Strategi Operasi Berbasis Lean Six Sigma sebagai Usaha Peningkatan Service Level - Sari, Rini Mulyani; Nugraha, Evan (Winaya Mukti University, 2019)
The development of the automotive industry in Indonesia made the level of competition even tighter, so Auto2000 Setiabudhi tried to provide periodic maintenance services, especially for the replacement of New Avanza Veloz disc brakes. The purpose of this study was to reduce the processing time of the New Avanza Veloz disc brake replacement to increase the Auto2000 Setiabudhi service level. However, the results of observations found that the time for disc brake replacement was exceeded the requirements set by the company. The observation was carried out for two years, from 2017 to 2018. Obtained also information from observations that there was an increase in the processing time gap of 0.84%, an increase in service level gap of 5.17%, while waste that occurred was waste waiting and motion. The method used in this study is based on Lean Six Sigma. The results obtained after improvements were made to a reduction in processing time by 50%, reduction in waste waiting, and motion and the achievement of service levels by 100%.